2009
DOI: 10.1111/j.1365-3083.2008.02222.x
|View full text |Cite
|
Sign up to set email alerts
|

Bronchoalveolar Lavage Fluid Cellular Characteristics, Functional Parameters and Cytokine and Chemokine Levels in Interstitial Lung Diseases

Abstract: Idiopathic pulmonary fibrosis (IPF), hypersensitivity pneumonitis (HP) and sarcoidosis belong to interstitial lung diseases (ILD) where an imbalance of regulatory, profibrotic and antifibrotic cytokines is hypothesized. The relationship of bronchoalveolar lavage (BAL) fluid (BALF) cytokines, BALF cell profile and ILD course is supposed. The aim of our study was to correlate BALF cytokine and chemokine levels with BALF cellular characteristics and lung function parameters in different ILD. Twenty‐two sarcoidosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 26 publications
1
45
1
Order By: Relevance
“…First, we did not observe any angiogenesis in pulmonary sarcoidosis, in contrast with other pulmonary inflammatory fibrotic processes [20]. This absence of angiogenesis is at variance with the expected findings, in light of the high levels of vascular endothelial growth factor in bronchoalveolar lavage fluids reported in sarcoidosis, and in epithelioid cells detected by immunohistochemistry and in situ hybridisation [21,22]. Conversely, macrophages are also known to secrete anti-angiogenic factors, such as endostatin/ collagen XVIII [23].…”
Section: Discussioncontrasting
confidence: 60%
“…First, we did not observe any angiogenesis in pulmonary sarcoidosis, in contrast with other pulmonary inflammatory fibrotic processes [20]. This absence of angiogenesis is at variance with the expected findings, in light of the high levels of vascular endothelial growth factor in bronchoalveolar lavage fluids reported in sarcoidosis, and in epithelioid cells detected by immunohistochemistry and in situ hybridisation [21,22]. Conversely, macrophages are also known to secrete anti-angiogenic factors, such as endostatin/ collagen XVIII [23].…”
Section: Discussioncontrasting
confidence: 60%
“…Effects of age and gender on serum CCL2 and CXCL8 concentrations were not significant. In humans, both CXCL8 and CCL2 concentrations were found to be increased in blood (Ziegenhagen et al, 1998a;Suga et al, 1999;Fujiwara et al, 2012) and bronchoalveolar lavage fluid (BALF) (Capelli et al, 2005;Antoniou et al, 2006;Baran et al, 2007) of IPF patients compared with healthy volunteers and correlated with lung function (Capelli et al, 2005;Emad and Emad, 2007;Martina et al, 2009;Vasakova et al, 2009), disease progression (Ziegenhagen et al, 1998b;Totani et al, 2002), and outcome (Shinoda et al, 2009;Richards et al, 2012). Furthermore, several studies suggested an involvement of the chemokine CCL2 in the pathogenesis of IPF, notably through its action on resident pulmonary fibroblast and circulating fibrocytes, promoting the generation of abundant extracellular matrix in the lungs (Gharaee-Kermani et al, 1996;Phillips et al, 2004;Moore et al, 2005;Inomata et al, 2014).…”
Section: Cxcl8 and Ccl2 Concentrationsmentioning
confidence: 99%
“…One hypothesis is pathogenic cytokine release. Tumor necrosis factor-α(TNF-α) and interleukins are thought to be the dominating contributing cytokines [9,10]. Recently there was case reported that Nod-like receptor pyrin domaincontaining protein 3(NLRP3)may act as an initiator of inflammation process in lung of R-ILD patient.…”
Section: Discussionmentioning
confidence: 99%